Utilização de lodo proveniente de estações de tratamento de água e de tratamento de esgoto para produção de tijolos: estudos de casos da Petrobrás e da Votorantim - Silva, Valdir Francisco da (Universidade Federal de São Carlos, 2021)
Water plays an important role in the industry and for its proper use in oil refining, prior treatment is necessary, as occurs in the Water Treatment Station of a Petrobras refinery, in Paulínia-SP (ETA / Replan), during which a chemical sludge is generated, which need an appropriate destination to avoid causing environmental impacts and not compromising their disposal sites. Another important component of the industries are the Sanitary Sewage Treatment Stations - ETEs, like the pulp and paper industry station, in Votorantim-SP (ETE / VCP), which also produce sludge, although more organic. Both the sludge from ETAs and ETEs must receive an adequate destination in order not to cause negative environmental impacts. Thus, the general objective of this work is to study the technical feasibility of incorporating the sludge from ETA / Replan and ETE - VCP into clayey clay for the manufacture of bricks. The study was carried out in partnership with a pottery that, in addition to red clays and slabs, used the sludge from ETA / Replan and ETE / VCP in the composition of the bricks. The equipment and procedures necessary for the analyzes were provided by external laboratories, as required by CETESB. Both waste from ETE / VCP and ETA / Replan were classified as Class II - non-inert and non-hazardous, which indicates a high potential for use as a raw material in construction materials. The addition of residues in the mortar did not significantly alter the water absorption of the bricks, which averaged 20.7%. There was an increase in compressive strength with the incorporation of the sludge residue from ETA / Replan around 9%, with an average of 12.4 Mpa. The results allow us to conclude that the residues added to the mortar are suitable for use in construction materials.
Use of sludge from water treatment plants and sewage treatment for brick production: case studies of Petrobras and Votorantim
Keywords: Resíduos Sólidos.; Lodo.; Estação de Tratamento de Água.; Estação de Tratamento de Esgotos.; Impactos ambientais.; ENGENHARIAS; ENGENHARIAS::ENGENHARIA SANITARIA::SANEAMENTO BASICO::RESIDUOS SOLIDOS, DOMESTICOS E INDUSTRIAIS